Late onset Ito's nevus - Resende, C (2013)
Dermal melanocytoses include a variety of congenital and acquired melanocytic lesions characterised by the presence of multiple spindle-shaped dendritic melanocytes in the dermis. These lesions are commonly found in the skin of Asians, but they can also appear in Caucasians. The Mongolian spot, nevi of Ota and Ito are the most common morphological forms. We report a case of a 24-year-old Caucasian woman presented with a 10-months history of progressive darkening of the right side of her upper back. Cutaneous examination revealed a macular blue-grey hyperpigmentation of the right side of her upper back. Biopsy specimen from the macule showed multiple darkly pigmented, spindle-shaped dendritic melanocytes in the superficial dermis, interstitially arranged between collagen bundles. The diagnosis of nevus of Ito was established. Our patient is maintaining vigilance in dermatology consultation.